Analisis dan Perancangan Sistem Informasi Akuntansi Pembelian dan Penjualan Menggunakan Microsoft Access 2021 pada CV Iphone by Sheila - Diandra Oliviani Almandita; Sugih Sutrisno Putra; Iyeh Supriatna; Endah Dwi Kusumastuti; Jouzar Farouq Ishak (Indonesian Accounting Literacy Journal, 2023)
The purpose of this research is to determine the buying and selling accounting information system implemented on CV Iphone by Sheila and to create a purchasing and selling application design using Microsoft Access 2021 software. This research was conducted with a qualitative descriptive method and uses the SDLC system development method as an analytical tool. The findings revealed that there were still some flaws in the company's operations, such as no purchase transaction recording, ineffective authorization systems and recording procedures, ineffective use of Microsoft Excel software, and the absence of an application that facilitates recording purchases and sales. Through this research, solutions to problems are provided, especially in terms of improving procedures and designing applications that are tailored to the circumstances and needs of the company, so that it is easier for businesses to record and search information, print sales invoices, and generate reports as needed.